Post-extraction maxillary lip entrapment in cats: a prospective study - Marx, Robert; Gracis, Margherita; Šparaš, Luka; Nemec, Ana (Frontiers in Veterinary Science, 2025)
ObjectiveTo investigate the prevalence, outcomes, and contributing factors of post-extraction maxillary lip entrapment (MLE) in cats, with a focus on anatomical and surgical technique-related variables.AnimalsThirty-seven client-owned cats undergoing maxillary canine tooth extraction between December 2022 and November 2024.ProceduresThis prospective study included cats undergoing maxillary canine tooth extraction performed by veterinary dental surgeons across three referral clinics. Specifically, we intended to explore the association between MLE and skull conformation, mandibular canine teeth crown height, distance between the crown tips of the maxillary and mandibular canine teeth, extent of maxillary canine alveolectomy, and presence/absence of caudal teeth on this clinical entity. Post-extraction MLE was classified as mild, moderate, or severe based on clinical findings and treatment requirements.ResultsPost-extraction MLE was observed in 26 cats (70.3%), with 23 of 26 cats (88.5%) being classified as having mild lesions, three (11.5%) with moderate lesions and none with severe lesions. Spontaneous improvement was noted in all mild cases. Only patients with moderate lesions required medical intervention. None of the evaluated factors had any statistically significant impact of the prevalence of MLE.Conclusions and clinical relevancePost-extraction MLE in cats is a frequent but predominantly mild and self-limiting complication. Conservative management typically suffices, and advanced imaging in future studies could enhance understanding of predisposing factors and surgical strategies, leading to improved patient outcomes.